Preparation and characterisation of Al-doped ZnO and PVDF composites - Ju Peihai; Weng Ling; Liu Lizhu; Zhang Xiaorui (High Voltage, 2016)
A single organic composite material having high dielectric constant is difficult to meet the needs of the market. Nowadays, polymer matrix-based composites have become a promising option that researchers are focusing on. Al-doped zinc oxide (ZnO) and composites containing ZnO as reinforcement and poly(vinylidene fluoride) (PVDF) as matrix were prepared. The microstructure of composites was analysed by scanning electron microscope and transmission electron microscopy techniques. The chemical structures and crystallisation behaviour of the materials were investigated by the means of FT-IR and X-ray diffractometer. ZnO, having both rod- and sheet-shaped, was evenly distributed within the PVDF material. Additionally, the dielectric properties and breakdown field strength of composite were tested. As the content of the fillers was kept steady, the dielectric constant of the composite material increased proportionally with the Al content. Thus, a composite containing 10% ZnO with 7% Al displayed a dielectric constant of 18.5 at 100 Hz, twice when compared with the pure ZnO/PVDF composites. This phenomenon was attributed to ZnO semiconductor properties which can significantly improve the conductive nature of the materials.